Analysis of Reject Part Adapter CN-235 (N70) - Permana, Sidik; Saepudin, Cepi; Kustaman, Usman; Purwana, Ega; Kamarudin, Udin (International Journal of Psychosocial Rehabilitation, 2020)
Part CN CN 235 (N70) adapter is a part for the infrared radar sensor seat holder or housing on the aircraft. This part requires high accuracy and there should be no mistakes in the manufacturing process. Analysis of Part Adapter damage is done because there is a discrepancy in the size of zone 30 that is the standard 0.5 micron while the result is 0.7 micron. The analysis was performed using the measurement protocol method on the Deckal Maho machine. The results of measurement analysis on the Deckal Maho machine showed a deviation on the C axis of 24 microns from a tolerance of -20 to 20 microns. Calibration is carried out on the C axis by using calyces geometry measurements and parameter settings for the input data on the Deckal Maho machine monitor. Calibration results on Axis C show deviations of -10 microns, still within tolerance.